Vitamin D Insufficiency with Elevated ADMA and hs-CRP: A Single-center Study of Chronic Kidney Disease Patients Undergoing Hemodialysis - Lusito, Lusito; Lestariningsih, Lestariningsih; Partiningrum, Dwi Lestari; Chasani, Shofa; Arwanto, Arwedi; Nurani, Ayudyah; Makarim, Fadhli Rizal (Indonesian Journal of Kidney and Hypertension, 2024)
Background: Vitamin D deficiency is a common issue among patients with chronic kidney disease (CKD) due to its ability to convert vitamin D into the active form of calcitriol, which is crucial for controlling cell inflammation. Low vitamin D levels are associated with increased inflammation and higher levels of biomarkers such as c-reactive protein and asymmetric dimethylarginine as an endogenous inhibitor of nitric oxide synthase. Those two combined become a specific marker for cardiovascular diseases, which become one of the common causes of CKD mortality. Objective: This study examines the correlation between vitamin D insufficiency, elevated high-sensitivity c-reactive protein, and asymmetric dimethylarginine in CKD patients receiving hemodialysis. Methods: This study used a cross-sectional design of CKD patients receiving hemodialysis in Dr. Kariadi Central General Hospital, Semarang, Indonesia, in November 2021. Thirty-six patients were randomly enrolled after meeting inclusion and exclusion criteria. Primary outcomes of Vitamin D, hs-CRP, and ADMA were measured from patients’ blood after hemodialysis. A statistical analysis of Pearson's correlation was used for primary outcomes. Results: No significant difference was found in the patient's baseline characteristics. A significant correlation between vitamin D and ADMA has been found; however, no correlation between vitamin D and hs-CRP has been found Conclusion: Vitamin D deficiency is correlated with elevated ADMA, indicative of endothelial dysfunction.